Suppression of Neuronal Firing Following Antidromic High-Frequency Stimulations on the Neuronal Axons in Rat Hippocampal CA1 Region - Yuan, Yue; Feng, Zhouyan; Yang, Gangsheng; Ye, Xiangyu; Wang, Zhaoxiang (Frontiers in Neuroscience, 2022)
High-frequency stimulation (HFS) of electrical pulses has been used to treat certain neurological diseases in brain with commonly utilized effects within stimulation periods. Post-stimulation effects after the end of HFS may also have functions but are lack of attentions. To investigate the post-stimulation effects of HFS, we performed experiments in the rat hippocampal CA1 region in-vivo. Sequences of 1-min antidromic-HFS (A-HFS) were applied at the alveus fibers. To evaluate the excitability of the neurons, separated orthodromic-tests (O-test) of paired-pulses were applied at the Schaffer collaterals in the period of baseline, during late period of A-HFS and following A-HFS. The evoked potentials of A-HFS pulses and O-test pulses were recorded at the stratum pyramidale and the stratum radiatum of CA1 region by an electrode array. The results showed that the antidromic population spikes (APS) evoked by the A-HFS pulses persisted through the entire 1-min period of 100 Hz A-HFS, though the APS amplitudes decreased significantly from the initial value of 9.9 ± 3.3 mV to the end value of 1.6 ± 0.60 mV. However, following the cessation of A-HFS, a silent period without neuronal firing appeared before the firing gradually recovered to the baseline level. The mean lengths of both silent period and recovery period of pyramidal cells (21.9 ± 22.9 s and 172.8 ± 91.6 s) were significantly longer than those of interneurons (11.2 ± 8.9 s and 45.6 ± 35.9 s). Furthermore, the orthodromic population spikes (OPS) and the field excitatory postsynaptic potentials (fEPSP) evoked by O-tests at ~15 s following A-HFS decreased significantly, indicating the excitability of pyramidal cells decreased. In addition, when the pulse frequency of A-HFS was increased to 200, 400 and 800 Hz, the suppression of neuronal activity following A-HFS decreased rather than increased. These results indicated that the neurons with axons directly under HFS can generate a post-stimulation suppression of their excitability that may be due to an antidromic invasion of axonal A-HFS to somata and dendrites. The finding provides new clues to utilize post-stimulation effects generated in the intervals to design intermittent stimulations, such as closed-loop or adaptive stimulations.